Create! - Arroyo, Eduardo, 1937-2018 (Actar, 2014)
This book shapes a thick network of experiences and crossed interests opened throughout last twenty-five years in the office NO.MAD and its founder Eduardo Arroyo. In its pages there are mixed reflections, anecdotes and creations that shape an exciting cocktail between living, thinking and creating. In some time of our physiological life something inside each one gets lost and the mind fills with doubts. In spite of the inertia of the long crossed distance, to stop and to look behind with exploratory smell can help us to enter with courage in the unknown days. This book shapes a thick network of crossed interests opened throughout last twenty-five years of the office NO.MAD and its founder Eduardo Arroyo. Topics like the origin and the memory, the soul and the precision, the random and the instability, the empathy, the instants and the choice, the hybridization and the blurry systems, the cloning, the invisible orders and the essential complexity or the combination of matter and energy turn out to be here interlaced. They shape a kaleidoscopic optics that though has guided always by an invincible illusion has never been exempt from the risk of diving in the unknown thing. The trip across these invisible paths demonstrates a critical vision of the world and the voluntary obligation to try to transform it from the creative independence, the determination and the valor that they are the transparent message of this book.